2020
DOI: 10.1002/jnm.2746
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network application for novel 3D printed nonuniform ceramic reflectarray antenna

Abstract: The main inconvenience in design process of modern high performance reflectarray antennas is that these designs are heavily depended on full-wave electromagnetic simulation tools, where in most of the cases the design optimization process would be an inefficient or impractical. However, thanks to the recent advances in computer-aided design and advanced hardware systems, artificial neural networks based modeling of microwave systems has become a popular research topic. Herein, design optimization of an alumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Existing research have shown that dielectric reflectarray have low loss and well performance in microwave frequencies, which can achieve ultra-wideband. [20][21][22][23][24] The dielectric reflectarray of literature 20 adopts the fused deposition modeling (FDM) printed to achieve reconfigurable polarization mechanically. The dielectric resonator reflectarray 21 achieved a gain of 28 dBi at 30 GHz in FDM printed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research have shown that dielectric reflectarray have low loss and well performance in microwave frequencies, which can achieve ultra-wideband. [20][21][22][23][24] The dielectric reflectarray of literature 20 adopts the fused deposition modeling (FDM) printed to achieve reconfigurable polarization mechanically. The dielectric resonator reflectarray 21 achieved a gain of 28 dBi at 30 GHz in FDM printed.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband circularly polarized dielectric reflectarray with cross-shaped dielectric unit, 23 and 3D-printed to achieve a maximum gain of 24.2 dBi in Ka-band. The reflectarray printed with alumina-based ceramic was applied to artificial neural network, 24 and the gain reached 24.2 dBi at 10 GHz with a diameter of 200 mm. A broadband high-gain dielectric reflectarray operating at 220 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 3D printing of ceramic components is more rapid and efficient than traditional forms, with a lower manufacturing cost for ceramic shapes. A prototype sample of a 3D clay printer is developed and utilized to verify its efficiency before use to create high-precision shapes or make patch antenna substrates [20][21][22]. The procedures of 3D printing with ceramics [23][24][25] are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the related work in literature on surrogate‐based modeling of microwave circuits and their applications can be named as follows: estimation of microwave transistors performance characteristics, 24‐28 prediction of reflection phase characteristic of reflect array antennas unit elements, 29‐31 for synthesis and analysis of microstrip lines, 32‐34 for estimation of a microstrip patch antenna's resonant frequency and modeling of microstrip antennas, 35,36 scattering parameter and frequency identification method for ANN‐based eye‐height/width prediction, 37 computationally feasible narrow‐band antenna, 38 and design optimization of microwave antenna designs 39‐43 …”
Section: Introductionmentioning
confidence: 99%